Dissection of the brain supplying arteries over the life span. Issue 8 (16th July 2004) - Ahl, B; Bokemeyer, M; Ennen, J C; Kohlmetz, C; Becker, H; Weissenborn, K
Abstract : Cervical artery dissection (CAD) is being increasingly diagnosed due to improved neuroimaging methods. The mean age of patients with CAD is about 40 years, with a peak between 40 and 45 years of age. Proven data on the incidence of CAD in older patients are missing. Therefore, whether CAD should also be considered as a probable cause of cerebral ischemic events in the elderly was investigated. All consecutive patients referred to our clinic with a diagnosis of cerebral ischemia from January 1999 until June 2000 were thoroughly assessed for the presence of CAD. In addition, the records of all stroke patients treated in our department from January 1995 to December 1998 were analysed retrospectively for a diagnosis of CAD. A total of 34 patients (11 women) had suffered from internal carotid (n = 29) or vertebral artery (n = 5) dissection. Their mean (SD) age was 50.3 (14.6) years, with 32.4% being older than 60 years. Clinical presentation of CAD did not differ depending on the patients' age. The results show that CAD is a possible cause of cerebral ischemia in the elderly and thus has also to be considered in the diagnostic investigation in this patient group.